Implementasi Mandatory Sertifikasi Halal terhadap Umkm Usaha Pemotongan Unggas di Desa Poter Kecamatan Tanah Merah - Jiwana Era Rahmadha; Karim, Moh (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Halal certification has an important role in micro, small and medium enterprises, especially in poultry slaughtering businesses. This certification refers to the recognition that the product meets Islamic sharia standards, which is very important for Muslim consumers. A poultry slaughterhouse is a place where the process of slaughtering animals such as chickens, ducks, geese, and others that are processed for meat occurs. This poultry slaughterhouse is usually equipped with various facilities to ensure that the slaughtering is carried out hygienically and in accordance with food safety standards. In this case, halal certification is very important, because it can be used as a reference in ensuring that all meat production processes are in accordance with Islamic sharia principles. The purpose of this study was to determine how the implementation of halal certification and mandatory halal certification for Poultry Slaughtering businesses, this study is expected to make poultry slaughtering business actors aware of the importance of halal certification in micro, small and medium enterprises in the poultry slaughtering business. One of the poultry slaughterhouse s in Poter Village, Tanah Merah District, which is the main place for slaughtering poultry to be studied. The research methodology used is qualitative with a field research approach, involving interviews and direct observation at the research location.